Mechanical Properties of New Ceramic Materials Obtained from Granular Solid Residuals Coming from Mines and Diatomaceous Earth - Vite-Torres, Jaime; León, María del Carmen Carreño de; Vite-Torres, Manuel; Laguna-Camacho, Juan Rodrigo (IntechOpen, 2011)
None